Genetic selection in Eucalyptus full-sibs families for charcoal production - Henriques, Eduardo Pinheiro [UNESP]; Pires Nunes, Andrei Caique; Teixeira de Moraes, Mario Luiz [UNESP]; Vilela de Resende, Marcos Deon; Sebbenn, Alexandre Magno; Moraes, Marcela Aparecida de (Ipef-inst Pesquisas Estudos Florestais, 2018)
The objective of this study was to evaluate a progeny test of Eucalyptus full-sib families at 2, 5 and 7 years of age to select parents and superior individuals in a reciprocal recurrent selection program in the state of Minas Gerais. The experimental design was a randomized complete block design with 286 full-sib families, eight replications and linear plots of six plants. The evaluated traits were height (ALT), diameter at breast height (DAP) and volume (VOL). The individual heritability in strict sense (h(a)(2)) for VOL and for all ages was approximately double the heritability of the dominance effects of the population (h(dom)(2)). The individual heritability in the broad sense (H-a(2)) for the VOL was medium (ranged between ages from 0.28 to 0.39), which indicates the possibility of genetic gains with selection within the population. A total of 256 individuals were selected from 32 families with a highest VOL (mean of 74.24 m(3).ha(-1).year(-1)) to establish a seed orchard and 65 progenies were selected for a hybrid seed orchard. Ten individuals with highest VOL were also selected (mean of 86.08 m(3).ha(-1).year(-1)). The genetic selection methodology used allowed the quantitative study of the full-sib population and the direction of future crosses for the reciprocal recurrent selection program in Minas Gerais.
Keywords: Genetic parameters; Progeny test; Reciprocal Recurring Selection